Religious politics in post-reformation England : essays in honour of Nicholas Tyacke - Tyacke, Nicholas; Fincham, Kenneth; Lake, Peter (Studies in modern British religious history ;, 2006)
The consequences of the Reformation and the church/state polity it created have always been an area of important scholarly debate. The essays in this volume, by many of the leading scholars of the period, revisit many of the important issues during the period from the Henrician Reformation to the Glorious Revolution: theology, political structures, the relationship of theology and secular ideologies, and the Civil War. Topics include Puritan networks and nomenclature in England and in the New World; examinations of the changing theology of the Church in the century after the Reformation; the evolving relationship of art and protestantism; the providentialist thinking of Charles I; the operation of the penal laws against Catholics; and protestantism in the localities of Yorkshire and Norwich. KENNETH FINCHAM is Reader in History at the University of Kent; Professor PETER LAKE teaches in the Department of History at Princeton University. Contributors: THOMAS COGSWELL, RICHARD CUST, PATRICK COLLINSON, THOMAS FREEMAN, PETER LAKE, SUSAN HARDMAN MOORE, DIARMAID MACCULLOCH, ANTHONY MILTON, PAUL SEAVER, WILLIAM SHEILS.